Out of place: thoracic splenosis—a case report - Gaston Becherano; Eitan Podgaetz; Shair Ahmed; Sigrid Ringenberg; Gary Schwartz (The Cardiothoracic Surgeon)
Abstract Background Thoracic splenosis is a rare condition where there is ectopic autotransplantation of splenic tissue, typically after traumatic injury of the spleen or splenectomy with or without history of diaphragmatic injury. This diagnosis is noteworthy, as fewer than 100 cases have been documented since its initial description in 1896. Additionally, the patient’s oncological background further complicated the diagnostic process. Case presentation We present a case of an asymptomatic 37-year-old male with a past medical history of a right testicular seminoma and a surgical history of splenectomy and left pneumothorax due to a motorcycle accident 18 years prior. During oncological surveillance, a computed tomography (CT) scan of the chest revealed a mediastinal mass, which raised concern for metastatic seminoma or a primary tumor. Surgical removal via a robotic-assisted thoracoscopic approach demonstrated thoracic splenosis. Conclusions Thoracic splenosis should be considered as a differential diagnosis of mediastinal masses in patients with history of traumatic spleen injury or splenectomy. Surgical resection may be necessary in oncological cases to rule out metastasis.